PROBLEM OF FORMING AND DEVELOPMENT OF INFORMATION COMPETENCE OF TEACHER-PHILOLOGIST IN WORLD PEDAGOGICAL EXPERIENCE AND IN UKRAINE - Nataliia V. Soroko (Інформаційні технології і засоби навчання, 2010)
The article is devoted to the problem of development of information competence of teacher-philologist in world pedagogical experience and in Ukraine. It has been offered the course «Basis of information competence», which efficiency was tested during an experiment in 2005 – 2008.